Psychomotor Features in Preschool Children - Zagrevskaya A.I; Sosunovsky V.S; Zalmezh T.N (Moscow State University of Psychology and Education, 2018)
The paper presents data of a research on psychomotor abilities in children aged 6-7 years (the sample included 109 children of Tomsk kindergarten #4 "Montessori) that was aimed at improving their teaching and physical training and providing recommendations for parents.The children's psychophysiological functions were studied using a special equipment called "Sports Psychophysiologist" (manufactured by "Analytic" research centre, Russia, Omsk).When considering the features of psychomotor development and physical education in children of preschool age, one must take into account the mutual connections between the types of the nervous system, perceived analyzers, age and sex of children.The results of the study enabled us to provide individual recommendations for parents to help them better understand their child's behaviour, assess the risks of psychological maladaptation at school, master the effective ways of stimulating and regulating motor activity, learn the optimal balance of work and rest for their children and the level of their stress resistance in new situations.